Moral Educational Values With Characters Contained in The Legend of The Hanging Stone of The Toba Batak Oral Literature - Manalu, Martini; Muhammad Angga Syabani; Muhammad Keny; Inka Amara Gustanti (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research seeks to explore the content of North Sumatra folklore specifically situated in Parapat. The participants underwent observations by examining storybooks in-depth. However, not all data could be thoroughly analyzed due to certain information not being presented. For instance, detailed aspects of the characters' lives were often absent, with the focus limited to everyday narratives outlined in the books.